Changes in Surgical Revascularization Strategy After Fractional Flow Reserve - Fournier, S (2021)
Aims: In the randomized GRAFFITI trial, surgeons drew their strategy based on coronary angiography. When patients were randomized to fractional flow reserve (FFR)-guidance, surgeons were informed of the FFR values and asked to redraw their strategy. The aim of this study was to investigate the changes induced by FFR knowledge. Methods and results: The intended and performed strategy (before and after FFR) were compared. Among 172 patients, 84 with 300 lesions were randomized to the FFR-guided group. The intended strategy was to bypass 236 stenoses:108 with a venous and 128 with an arterial graft. After disclosing FFR, a change in strategy occurred in 64 lesions (21.3%) of 48 (55%) patients. Among 64 lesions for which the intended strategy was medical therapy, 16 (25%) were bypassed after disclosing FFR. The number of procedures with >1 venous graft planned was significantly reduced from 37 to 27 patients (p = .031). The proportion of on-pump surgery was significantly reduced from 71 to 61 patients (p = .006). The rates of clinical events at 1 year were similar between patients with or without at least one change in strategy. Discussion: FFR-guided CABG is associated with a simplified surgical procedure in 55% of the patients, with similar clinical outcomes.